Local and central testing for HER2, PD-L1, MSI/MMR, EBV, and CLDN18.2 in advanced gastric cancer: results from the SAPHIR registry☆ - K. Potthoff; H. Bläker; T. Dechow; A. Binninger; K. Ringwald; R. de Buhr; E. von der Heyde; M.-O. Zahn; A. Nusch; S. Dörfel; H. Schulz; I. Haffner; et al. (ESMO Real World Data and Digital Oncology)
Background: Predictive biomarkers guide treatment selection of patients with advanced gastric and gastroesophageal junction adenocarcinoma (GAC/GEJAC). However, real-world data on testing frequencies and prevalence of biomarkers in Europe are limited. Methods: The SAPHIR registry, a prospective, observational cohort study of patients with metastatic GAC/GEJAC, collects longitudinal clinical data, patient-reported outcomes as well as tumor tissue samples from routine diagnostics. Here, we focus on biomarker testing and test results in routine clinical practice. In addition, central pathology assessment was performed for HER2, PD-L1, dMMR/MSI, EBV, and CLDN18.2. Results: From December 2019 until March 2022, a total of 473 evaluable patients were enrolled at 109 study sites in Germany. Their median age was 66.8 years, 73.6% were male, and 76.7% had an ECOG performance status of 0/1. In clinical routine, testing rates for HER2, PD-L1, MSI, EBV, and MMR were 78.6%, 31.3%, 15.6%, 4.9%, and 2.5%, respectively. CLDN18.2 was not tested during the respective period. By central testing, the positivity rates were 11.8% for HER2, 75.2% for PD-L1 (CPS ≥1, TPS/IC ≥1%), 2.5% for dMMR/MSI-H, 0.6% for EBV, and 26.7% for CLDN18.2. Deviations between local and central testing were 12.4% for HER2 and 22.4% for PD-L1. Conclusions: This study provides valuable insights on molecular testing in patients with GAC/GEJAC in Germany. In real-world, patients were frequently tested for actionable alterations, but there is room for improvement. Deviating test results of HER2 and PD-L1 by local and central pathology may reflect limitations in testing methodologies. In addition, these patients might not receive the most effective treatment.